Brain natriuretic peptide and optimal management of heart failure - 李楠 王建安 (Journal of Zhejiang University. B. Science, 2005)
Aside from the important role of brain natriuretic peptide （BNP） in diagnosis, and differential diagnosis of heart failure, this biological peptide has proved to be an independent surrogate marker of rehospitalization and death of the fatal disease. Several randomized clinical trials demonstrated that drugs such as beta blocker, angiotensin converting enzyme inhibitor, spironolactone and amiodarone have beneficial effects in decreasing circulating BNP level during the management of chronic heart failure. The optimization of clinical decision-making appeals for a representative surrogate marker for heart failure prognosis. The serial point-of-care assessments of BNP concentration provide a therapeutic goal of clinical multi-therapy and an objective guidance for optimal treatment of heart failure. Nevertheless new questions and problems in this area remain to be clarified. On the basis of current research advances, this article gives an overview of BNP peptide and its property and role in the management of heart failure.